PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA ALPHA HOTEL PEKANBARU - Resna Handayani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted by Alpha Hotel Pekanbaru located in the street of Imam Munandar (Harapan Raya), Simpang Sudirman No.17, 28282 Pekanbaru. This study aims to determine the effect of career development and work motivation on employee job satisfaction at Alfbaru Hotel pekanbaru.In this study the method used was quantitative descriptive with the SPSS program ver. 17 for Windows. The population in this study were all employees at the Alpha Hotel Pekanbaru, which numbered 71 employees. The sample in this study was taken using the census method, namely 71 employees. Methods of data collection using questionnaires (questionnaire) and free interviews. Hypothesis testing uses multiple linear analysis methods with the results of research namely Y = 2.459a + 0.327X1 + 0.652X2The research that has been done shows the results that respondent's response to career development, work motivation in good category. While for the t test that has been done shows that career development variables and work motivation partially have a significant effect on employee satisfaction. And the results of the F test show that career development and work motivation are simultaneously. And for the calculation of the determination coefficient (R2), the R Square value is 0.927, for employee job satisfaction. This shows that career development and work motivation have an effect of 92.7% on employee job satisfaction, while the remaining 7.3% is influenced by other variables not examined in this study. Keywords: Career Development, Work Motivation, Employee Job Satisfaction